The Relationship between Inpatient Expectations of Staff Responsiveness and Empathy with Inpatient Satisfaction at Wangaya District Hospital Denpasar - Dwidyaniti Wira; I Ketut Suarjana; I Putu Ganda Wijaya (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: The evaluation of quality of service within inpatient and outpatient services is very critical to be done. This research aims to explore the relationship between inpatient expectations of the quality of nursing service and inpatient satisfaction, in the third-class ward Wangaya District General Hospital, Denpasar. Methods: This research was a quantitative study using cross-sectional design. A sample of 111 were selected by simple random sampling. The data was analysed by using univariate, bivariate, and multivariate analysis with logistic regression. Results: The analysis indicated that the level of actual satisfaction compared to inpatient expectations was as low as 45%. Perception of responsiveness with OR=2.404 (95%CI: 1.076–5.373) and perception of empathy with OR=2.594 (95%CI: 1.165-5.779) had a significant relationship with inpatient satisfaction. Conclusion: The study concluded that the patient satisfaction rate is moderate and found to have significant correlation with perceptions of responsiveness and empathy.